FORMAÇÃO PROFISSIONAL EM EDUCAÇÃO FÍSICA: APROXIMAÇÕES E DISTANCIAMENTOS NA RELAÇÃO TEORIA E PRÁTICA NO CAMPO DO ESTÁGIO SUPERVISIONADO - Honorato, Ilma Célia Ribeiro (2011)
This research presents the understanding of how occurs the articulation between academic and theoretical practice formation and pedagogical practice together with the living of the discipline of Advised Trainee in Physical Education the schools into two College Graduation Institutions‟: one of public nature and the other of private nature. The research objectives were: a) investigate the possibility of come close with the academic knowledge to the pedagogical practice in the school by means of the living proposed by the discipline of Advised Trainee; b) revel the elements that focus on/out the academic formation from the pedagogical practice; c) support a list of items to build a critical reflection that corroborates to the improvement in order to grab the theory and practice, specially, in the curricular proposal which advise the graduation of pre service Physical Education teachers.The theoretical support to this work was built beyond the studies conducted by: Critical Curricular theories (SACRISTÁN, 2000; APLLE, 2002; 2005; GIROUX, 2005) and the College and its space of interlocution with different universes in which it is build (VEIGA, 2004, 2010; SANTOS 2005; CHAUÍ, 2001; PIMENTA; ANASTASIOU, 2002); the discipline of Advised Trainee as a space of interlocution between the theory and the practice (CANDAU, 1987; PIMENTA, 1997; SOUZA JUNIOR 2005; BORGES, 2010) the professional formation in Physical Education (FARIA JUNIOR, 1987, 1992; TAFFAREL, 1993; SANTOS JUNIOR, 2005). It was considered the curricular composition by means of legal Act related to Physical Education. The methodological option was constructed by means of qualitative research (LUDKE; ANDRÉ, 1986; THOMAS; NELSON; SILVERMAN, 2007; GIL, 2009). The planning was done covering a case study, more specifically a multi case (YIN, 2005). The research participants were four College Professors, whose were responsible for the Advised Trainee discipline, as well as, forty nine pre service teachers attending classes in the Course of Physical Education Graduation. The chosen research instruments were: documental analysis of Pedagogical Projects´ Course (PPC); direct enterview to the professors and in service teachers; questionnaires with open questions to the service teachers. The option related to the data analysis and discussion was based on the subject (BARDIN, 1977). The methodological strategy chosen to corroborate with the subject analysis was to cross out the data. The results discussion shed lights on Critical theory Curriculum. From the perspective of dialog about Physical Education Teachers´ Formation by means of the discipline of two colleges Advised Trainee, it was noticed that the conception of Curriculum is yet, a pattern that had an attempt to overcame in the decade of 1990 and triangular picture that had as intention to built, taking into account the three research instruments, It was not constructed , once that in the current process, it was reveled that it has a great amount of focus that go on and out the untidily about theory/practice of the discipline of Advised Trainee going on the concept of the Curriculum, in the statements concerned with Graduation Institutions, in the superficial comprehensions of the Professors` staff related to the elaboration of Pedagogical Project Course and in the Professors` Identity of the Formational Institution and the pre service teacher in the school.